Photoacclimation strategies in cyanobacterial photosynthesis under dynamic light environments: implications in growth, fitness, and biotechnological applications - Tiwari, Sapna; Gupta, Anjali; Pandey, Deepa; Pandey, Priyul; Gupta, Rinkesh; Singh, Shailendra Pratap (Frontiers in Microbiology, 2025)
Cyanobacteria, ancient oxygenic photoautotrophs originated in the Precambrian period, exhibit remarkable adaptability to diverse ecological systems. Light, a critical environmental factor, exerts differential pressures on these organisms. The scattering of white light creates dynamic light environments, which poses a significant ecological challenge. To thrive in dynamic light environment, cyanobacteria have developed several light acclimation strategies. This includes chromatic acclimation, which optimize light harvesting by adjusting pigments. Cyanobacteria also employ robust photoprotective mechanisms against quantitative light stress. Under high light, these organisms activate non-photochemical quenching using the proteins such as orange carotenoid protein, iron starvation-induced protein, and high light-induced proteins to safely dissipate excess excitation energy. Additionally, thylakoid-localized respiratory enzymes alleviate electronic pressure arising from over-reduction of the plastoquinone pool. Under low light conditions, cyanobacteria frequently employ state transitions, reversibly associating their phycobilisomes with PSII and PSI to optimize light harvesting. These natural strategies offer a blueprint for engineering cyanobacteria and algae for their application in biomanufacturing and CO2 sequestration. This review synthesizes the key light acclimation and photoprotective mechanisms, underscoring their importance for both the ecological success of cyanobacteria and their implication in biotechnological applications using engineered strains.